Transcriptomic profiling of recessive dystrophic epidermolysis bullosa wounded skin highlights drug repurposing opportunities to improve wound healing - Onoufriadis, Alexandros; Proudfoot, Laura E.; Ainali, Chrysanthi; Torre, Denis; Papanikolaou, Maria; Rayinda, Tuntas; Rashidghamat, Ellie; Danarti, Retno; Mellerio, Jemima E.; Ma’ayan, Avi; McGrath, John A. (Experimental dermatology, 2022)
Chronic wounds present a major disease burden in people with recessive dystrophic epidermolysis bullosa (RDEB), an inherited blistering skin disorder caused by mutations in COL7A1 encoding type VII collagen, the major component of anchoring fibrils at the dermal‐epidermal junction. Treatment of RDEB wounds is mostly symptomatic, and there is considerable unmet need in trying to improve and accelerate wound healing. In this study, we defined transcriptomic profiles and gene pathways in RDEB wounds and compared these to intact skin in RDEB and healthy control subjects. We then used a reverse transcriptomics approach to discover drugs or compounds, which might restore RDEB wound profiles towards intact skin. Differential expression analysis identified >2000 differences between RDEB wounds and intact skin, with RDEB wounds displaying aberrant cytokine‐cytokine interactions, Toll‐like receptor signalling, and JAK‐STAT signalling pathways. In‐silico prediction for compounds that reverse gene expression signatures highlighted methotrexate as a leading candidate. Overall, this study provides insight into the molecular profiles of RDEB wounds and underscores the possible clinical value of reverse transcriptomics data analysis in RDEB, and the potential of this approach in discovering or repurposing drugs for other diseases.